2016
DOI: 10.1097/wco.0000000000000380
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral self-management strategies for practice and exercise should be included in neurologic rehabilitation trials and care

Abstract: Purpose Rehabilitation trials and post-acute care to lessen impairments and disability after stroke, spinal cord injury, and traumatic brain injury almost never include training to promote long-term self-management of skills practice, strengthening and fitness. Without behavioral training to develop self-efficacy, clinical trials and home-based therapy may fail to show robust results. Findings Behavioral theories about self-management and self-efficacy for physical activity have been successfully incorporate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
86
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 93 publications
(93 citation statements)
references
References 55 publications
3
86
0
4
Order By: Relevance
“…29 increases as self-management progresses successfully. 30 CSE plays a significant role in both moderating and mediating effects on the well-being of caregivers. Studies have demonstrated that CSE has moderating effects on physical and psychological health as well as the coping ability of caregivers.…”
Section: Effects Of Dyadic Interventions On Pwd and Caregiversmentioning
confidence: 99%
See 1 more Smart Citation
“…29 increases as self-management progresses successfully. 30 CSE plays a significant role in both moderating and mediating effects on the well-being of caregivers. Studies have demonstrated that CSE has moderating effects on physical and psychological health as well as the coping ability of caregivers.…”
Section: Effects Of Dyadic Interventions On Pwd and Caregiversmentioning
confidence: 99%
“…Caregiving self‐efficacy refers to caregivers' beliefs that they can perform confidently and are capable of responding to the demands of caregiving and is considered a key determinant of emotional and behavioural response to stressors . It has been found that CSE increases as self‐management progresses successfully . CSE plays a significant role in both moderating and mediating effects on the well‐being of caregivers.…”
Section: Introductionmentioning
confidence: 99%
“…28 Self-management training to develop self-efficacy for the practice of skills and exercise appears to be necessary and should be considered as a routine strategy in clinical trials and early post stroke care. 29,30 …”
Section: The Problemsmentioning
confidence: 99%
“…4 With the continuous, objective measurements of change during real-world activity that are provided by devices, therapists gain potentially powerful behavioral intervention technologies that, for the first time, enable personalized, remotely managed rehabilitation during clinical trials and post-inpatient care. 5 …”
mentioning
confidence: 99%
“…5 With remote technology-supported trials, the therapist has a tool to teach self-efficacy for training. Telerehabilitation interactions based on monitoring devices can reinforce the person’s understanding of the health benefits of greater physical activity; identify possible personal and environmental barriers to activity and practice; teach problem solving; use behavioral intervention techniques such as goal setting, feedback about performance drawn from sensor data, tailored instruction, and reassessment of goals no less than once a week; and provide ongoing personal social support.…”
mentioning
confidence: 99%